Dato Sri Edmund Langgu anak Saga : ...seorang pemimpin dan pejuang - Neilson Ilan Mersat; Spencer, Empading Sanggin (Kota Samarahan, Sarawak : Universiti Malaysia Sarawak, 2011)
Biography of Edmund Langgu anak Saga, a politician from Sarawak, Malaysia.
Includes bibliographical references (pages 335-338) and index.
Keywords: Edmund Langgu anak Saga; Politicians -- Malaysia -- Sarawak -- Biography; Iban (Bornean people) -- Social life and customs